Improving the early properties of treated soft kaolin clay with palm oil fuel ash and gypsum - Al-hokabi, Abdulmajeed; Muzamir, Hasan; Amran, Mugahed; Fediuk, Roman; Vatin, Nikolai Ivanovich; Klyuev, Sergey (MDPI, 2021)
Soft soil problems and increased production of fuel waste have emerged due to world population growth. These two problems are prompting engineers to introduce new methods of using waste fuel to stabilize the soil. Previous research has shown clear sustained improvements in soil properties using palm oil fuel ash (POFA) when mixed with a calcium-based binder such as NaCl, lime or cement. The use of such a stabilizing agent can reduce the economic problems associated with reducing the cost of waste disposal and create a sustainable ecological system. It is an alternative method of replacing part of the soil to ensure a balance between economic growth and ecological privilege, leading to the achievement of green technology goals. However, this research is aimed at improving the properties of processed soft kaolin clay with a combination of POFA and gypsum. The physical and mechanical properties of all samples were tested. The results showed a decrease in the specific gravity with the addition of POFA and an increase with gypsum alone, as well as a decrease with a mixture of POFA and gypsum and a decrease in the soil plasticity index due to a better increase in the plasticity limit compared to the liquid limit. This is considered a sign of improved geotechnical properties and reduced linear shrinkage. It was also shown that the treated clay showed an increase in the optimal water content and a drop in the maximum dry density. Nevertheless, it can be concluded that the initial properties of the processed soft kaolin clay with the addition of POFA can be significantly improved